African Christian studies - Catholic Higher Institute of Eastern Africa. Faculty of Theology (Nairobi, Kenya : CUEA Publications, 2001)
Occasional papers will offer a synthesis of various CHIEA seminars, conferences by visiting lecturers, and workshops of an interdisciplinary nature.
Issued by: the Faculty of Theology of the Catholic Higher Institute of Eastern Africa, Nairobi.
SERBIB/SERLOC merged record
Keywords: Catholic Church -- Africa -- Periodicals; Catholic Church; Christianity -- Africa -- Periodicals; Christianity; Religion; Africa -- Religion -- Periodicals; Africa; Periodicals